Organoleptic Test and Consumer Preference Level of Red Dragon Fruit Goat Milk Yoghurt (Hylocereus polyrhizus.L.) with The Addition of Various Levels of CMC (Carboxy Methyl Cellulose) Stabilizer - Fitriani, Devi; Zulaikhah, Siti Rahmawati; Luthfi, S.A. Chayatul (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2025)
The purpose of this study was to determine the effect of adding various levels of CMC stabilizer on organoleptic properties (color, taste, aroma, texture) and consumer preference levels. The study involved 30 untrained panelists. This study was conducted using a Completely Randomized Design (CRD) using 4 Treatments and 5 replications. The treatments tested were the addition of different CMC stabilizer levels R1 = 0% (w/v), R1 = 0.3% (w/v), R3 = 0.6% (w/v), R4 = 0.9% (w/v). The variables observed were the organoleptic properties of color, taste, texture, aroma and consumer preference for red dragon fruit yoghurt. The results of the study showed that the addition of various levels of CMC stabilizer had a significant effect (P<0.05) on the color, aroma, texture, and consumer preference for red dragon fruit yoghurt. The highest value was the addition of 0.9% CMC with attractive color, typical yoghurt aroma, very thick texture, and was liked by consumers. The lowest assessment of color, aroma, texture and consumer preferences was the addition of 0.3% CMC with a rather attractive color, typical yoghurt aroma, liquid texture, and somewhat liked by consumers. The conclusion of this study is that yoghurt that has good color, aroma and texture values ​​and is preferred by panelists is yoghurt added with 0.9% CMC. The addition of CMC does not affect the taste of yoghurt.